A composite upstream sequence motif potentiates tRNA gene transcription in yeast. - Giuliodori, S; Percudani, R; Braglia, P; Ferrari, R; Guffanti, E; Ottonello, S; Dieci, G (2003)
Transcription of eukaryotic tRNA genes relies on the TFIIIC-dependent recruitment of TFIIIB on a approximately 50 bp region upstream of the transcription start site (TSS). TFIIIC specifically interacts with highly conserved, intragenic promoter elements, while the contacts between TFIIIB and the upstream DNA have long been considered as largely non-specific. Through a computer search procedure designed to detect shared, yet degenerate sequence features, we have identified a conserved sequence pattern upstream of Saccharomyces cerevisiae tDNAs. This pattern consists of four regions in which particular sequences are over-represented. The most downstream of these regions surrounds the TSS, while the other three districts of sequence conservation (appearing as a centrally located TATA-like sequence flanked by T-rich elements on both sides) are located across the DNA region known to interact with TFIIIB. Upstream regions whose sequence conforms to this pattern were found to potentiate tRNA gene transcription, both in vitro and in vivo, by enhancing TFIIIB binding. A conserved pattern of DNA bendability was also revealed, with peaks of bending propensity centered on the TATA-like and the TSS regions. Sequence analysis of other eukaryotic genomes further revealed the widespread occurrence of conserved sequence patterns upstream of tDNAs, with striking lineage-specific differences in the number and sequence of conserved motifs. Our data strongly support the notion that tRNA gene transcription in eukaryotes is modulated by composite TFIIIB binding sites that may confer responsiveness to variation in TFIIIB activity and/or concentration.